Thyroid disorders in pregnancy: prevalence and its fetomaternal outcome in a tertiary hospital of Delhi, India - Bansal, Neha; ., Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study was conducted to determine the feto maternal outcome in pregnant women with thyroid disorders. The prevalence of thyroid disorders in present study was 15.75%. Methods: This was a prospective observational study carried out in all pregnant women irrespective of their parity, who attended ANC clinic in department of obstetrics and gynaecology in a tertiary care hospital over a period of 2 years. After registering, the patients were followed up with routine antenatal visits up to delivery and records were reviewed for development of abortion, PIH, preterm delivery, GDM, anemia, placental abruption, still birth, anomalies, fetal distress, meconium stained liquor, low birth weight and neonatal outcome by neonate Apgar score and TSH value. Results: Mean age group in our study was 27.61±3.14. Family history was present in 8% of study group versus 0% in control group which was statistically significant (p=0.028). Eighteen percent of preeclampsia was diagnosed in study group as compared to 4% in control group which was statistically significant (p-value= 0.005). Fourteen percent patients had preterm labour in study group as compared to 6.7% in control group which was statistically significant (p value= 0.047). Increased neonatal TSH was found in study group (61.3%) as compared to control group (32%), this difference was statistically significant (p-value <0.001). There was increased importance of measuring TSH in first trimester as it was statistically significant in study group (p-value <0.001). Conclusions: All pregnant women should be screened for hypothyroidism as early as possible or before conception to prevent any fetomaternal complications.